OSCILLATORIA AMPHIBIA – SURSĂ DE SUBSTANŢE BIOLOGIC ACTIVE - Melniciuc, Cristina; Ungureanu, Laurenţia (CEP USM, 2011)
Nature, quantity of biochemical analysis of Oscillatoria amphibia Ag CLHE-A 1 were examined. These cultureswere grown in medium Gromov nr. 6, on the 14th day, after which laboratory analyses have been carried out. The eiochemical analysis of Oscillatoria amphibia biomass showed presence of (21,6%) protein, (1,4%) carbohydrates, and (17,18%) lipids. The high content protein indicates relatively good amino acid profile- essential et nonessential.
Keywords: tulpina Oscillatoria amphibia; aminoacizi